The Effect of Transformational Leadership and Organizational Culture on Organizational Innovation Through Employee Creativity as an Intervening Variable “Study on the Jurisdiction of the West Papua High Court” - Tanga, Alfrids; Erari, Anita; Handoyo , Sarwo Edy (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research focuses on analyzing the impact of transformational leadership and organizational culture on employee creativity and organizational innovation in the West Papua High Court Jurisdiction. The type of research used is quantitative research method with causality analysis. Data was collected by utilizing a questionnaire. In the data processing process to calculate each indicator, a Likert scale was used. Furthermore, validity and reliability tests were carried out. Data analysis was carried out by descriptive analysis and SmartPLS Analysis. The results showed that partially, transformational leadership has no effect on employee creativity, organizational culture partially has a positive effect on employee creativity, partially transformational leadership has no effect on organizational innovation, partially, organizational culture affects organizational innovation, and employee creativity partially has no effect on organizational innovation, partially, transformational leadership intervened by employee creativity has no effect on organizational innovation, and partially, organizational culture intervened by employee creativity has no effect on organizational innovation. Suggestions, it is good for organizations to improve the quality of transformational leadership, and need to pay attention to values, norms, and behaviors that encourage creativity.